Laravel Api Masterclass: Autentikasi, Role-Based Access and Crud Testing - Apriliano, Yova Rezky; Azima, Fauzan; Zahran, Fikry Muhammad; Zikri, Muhammad; Risanty, Rita Dewi; Sutrisno, Mirza; Mujiastuti, Rully; Nurbaya Ambo, Sitti; Ardharani, Yana (Society : Jurnal Pengabdian Masyarakat, 2025)
The latest developments in web technology require mastery in the development of well-planned and secure APIs as a foundation for integrating various digital systems. However, many new developers have difficulty in understanding the basic principles and practices of creating web-based APIs. To fulfil this need, the service team organised an event entitled "Laravel API Masterclass: Authentication, Role-based Access, and CRUD Testing" which aims to introduce the basics of API development using the Laravel framework to participants with various backgrounds. This activity was organised in the form of Webinars and Workshops, which included the delivery of theoretical material on API concepts, Laravel project structure, and role-based authentication and access control, followed by hands-on practical sessions from setting up to testing APIs using Postman. Through this programme, participants are expected to build a strong foundation for creating APIs that meet industry standards and are ready to be applied in small to medium-sized web application development.